Editorial Strategy in the Production of the Latest Covid-19 News Info During the Pandemic (Case Study on TVRI Jakarta) - Nunuk Parwati (Jurnal Imiah Teknik Studio, 2022)
Producing and broadcasting messages and information about the Covid-19 pandemic for TV broadcasting stations is certainly not easy. This requires an editorial strategy in assigning and broadcasting news about Covid-19. TVRI (Television of the Republic of Indonesia) as a public broadcasting institution from the beginning has prioritized Covid-19 news and the government's countermeasures. TVRI responded to the situation by creating the Latest Covid-19 News Info program which initially had a purpose to provide the fastest and most complete information to the public. This prompted the author to conduct a review of the editorial strategy in the program. This research used descriptive qualitative method. Based on the analysis of the Editorial Strategy in the Production of the Latest Covid-19 News Info : (1) The main idea of the program is to pursue the speed of news or the actuality of Covid-19 information. (2) The idea is supported by the board of directors with a policy of not applying budget refocusing, supporting health financing for all news crews, as well as providing equipment to broadcast live via the internet network with a bonding cellular device connected to a camera. (3) The Latest Covid-19 Info Program is experiencing challenges; a number of crew were exposed to Covid-19, delayed in sending news from several regions to Jakarta resulting in news repetition, (4) Program’s name containing the word 'Latest' on the one hand has advantages compared to similar programs. But the consequences are even more severe because the actuality is demanded. Even if the condition of the Covid case has decreased, it is possible that the news of Covid-19 will decrease and the program name may have to be changed.